Characterization of phenotypic diversity of a medicinal plant Lunasia amara - RIA CAHYANINGSIH (Smujo International, 2016)
Abstract. Cahyaningsih R. 2016. Characterization of phenotypic diversity of a medicinal plant Lunasia amara. Nusantara Bioscience 8: 245-251. Characterization of phenotypic diversity is an important first step in the conservation of plant species and in plant breeding for human purposes. Lunasia amara Blanco (‘kemaitan’, ‘sanrego’) is a medicinal plant native to Indonesia, used traditionally as an aphrodisiac. However, there is little knowledge about genetic diversity in this species, and even its taxonomic status remains under review. The study reported here describes and classifies phenotypic diversity among Lunasia amara and its relatives, focusing on vegetative characters assessed in the extensive collection of the species held in Indonesian Botanic Gardens. Based on results of a similarity analysis using SIMQUAL (Similarity for Qualitative Data) employing SM (Simple Matching Coefficients), the accessions exhibit low phenotypic diversity as indicated by high similarity coefficients. Nevertheless, the accessions could be divided into two not very distinctive groups. Based on PCA (Principal Component Analysis), none of the observed characters were of outstanding significance in partitioning the diversity among the accessions. Due to their high similarity value, and despite the wide geographic area represented in the accessions, the study lends support to the belief that they belong to a single taxon, Lunasia amara var. amara. For conservation of Lunasia spp, this study suggests further collection activity is not a priority. Studies on the quantitative content of medicinally active constituents as well as phylogenetic studies of molecular diversity would test this conclusion and support a plant breeding program to develop the usefulness of this plant for human purposes.